Shakespeare & Company – merging the Bard with the Russian via two female Brits. Issue 1 (2nd January 2018) - Merlin, Bella
Abstract: Shakespeare & Company was founded in Lenox, Massachusetts, in 1978 by English-born actor Tina Packer and Scots-born voice guru Kristin Linklater, in collaboration with Dennis Krausnick and Kevin Coleman. Since their founding, the Company's mission has forged an equal commitment to the three strands of actor training, performance and education. This paper (the core of which was presented originally at The S Word: Merging Methodologies symposium at DAMU, Prague, March 2017) is in many ways the precursor to a book currently being authored by Packer and Merlin, on the vision, aesthetics and pedagogy underpinning the Company's three strands. Merlin has worked as an actor with Packer ( Richard III, The Merchant of Venice, and Cymbeline ) as well as participating in S&Co's acclaimed Month-Long Intensive actor-training programme for mid-career professionals in January 2016. Packer's pioneering contribution to the female voice in theatre practice, acting processes and Shakespeare scholarship included her production of Cymbeline in summer 2017, which completed her directing and/or acting of Shakespeare's entire canon (an achievement arguably unprecedented by any other female practitioner – and by many males for that matter). Her dedication to freeing the natural voice and body, and speaking one's truth intricately merges with Stanislavski's psychophysical acting "system" and the "creation of the living word." In this paper, Merlin touches upon the history of Packer's work and provides a brief overview of the key components of the Month-Long Intensive. It also elucidates some of the crossovers and mergers between S&Co's practices and Stanislavski's principles, chiefly Active Analysis.